Partial disassembly sequence planning based on cost-benefit analysis. (15th December 2016) - Smith, Shana; Hsu, Li-Yen; Smith, Gregory C.
Abstract: Due to growing concern for the environment, green design methods are used to create products that can reduce resource use and environmental impacts, throughout the entire product lifecycle. In particular, the end-of-life stage of the product lifecycle has received much attention recently. Disassembly sequence planning is one of the major product end-of-life methods, which can be used to increase the reuse rate of components and reduce product environmental impacts. However, total disassembly is usually expensive and impractical. Contrary to total disassembly, this study develops a new partial disassembly sequence planning method. Most prior partial disassembly sequence planning methods did not use life cycle impact assessment tools to perform cost-benefit analyses to find an optimized disassembly stopping point. In this study, Simapro Eco-indicator 99 is used to analyze environmental impacts. The proposed method considers part order, part disassembly directions, number of reorientations, and number of tool changes to find an optimized disassembly plan and an optimized disassembly stopping point. Study results show that the proposed partial disassembly sequence planning method can be used to reduce environmental costs and increase economical benefits, compared to the traditional disassembly methods. Study results also show that the method can help designers redesign the products, make the parts with high economical (recycling) benefits more accessible, and reduce disassembly cost.